(untitled) (Journal Intellectual Sufism Research (JISR), 2024)
Education has essentially emerged since the creation of humans. The development of education is called a period. In Islamic education, there is a period of Islamic education development, which took place during the time of the Prophet Muhammad. So this article aims to find out the management of Islamic education during the time of the Prophet Muhammad. The research method used in writing this research is the qualitative method of literature study. The results of this study are Islamic civilization and thought during the time of the Prophet Muhammad. Developing in two periods, namely the Mecca period and the Medina period. Both periods also developed civilization and thought in various fields, including the following: intellectual field, social and economic fields, as well as political and legal fields. The legal structure in Mecca and Medina was held by the Prophet Muhammad. The legal substance is in the form of the Koran and hadith, both of which come from the revelation of Allah SWT. Legal culture shows that the people of Mecca and Medina obey the law. This obedience is influenced by strong beliefs. Keywords: management, Islamic education, the time of the Prophet